Developing Students’ Speaking Skills through Recap(ping) - Shrestha, Parshu Ram (Journal of Janta Multiple Campus, 2025)
Recap(ping) is a practice of summarizing and reflecting upon the activities conducted during a lesson. A teacher can choose to conduct this activity either at the beginning, or at the end of a lesson. As an English language teacher, I have been using recapping as a signature pedagogy since the beginning of my teaching career. In this article, I have examined my long-time practice of recapping activity in my English language classroom using analytical-interpretive autoethnography. I have narrated and analyzed my memory data of using recapping activity in my English language classroom to discuss its usability, pedagogic importance, merits, and demerits as a signature pedagogy. This study underscores the effectiveness of recapping as a pedagogic tool with its high adaptability and multiple benefits for both the teachers and the students.